Malachite Green Removal by Grape Stalks Biosorption from Natural Waters and Effluents - Lemos, Eliana Soledad (2023)
The efficiency of the grape stalk as a biosorbent for the malachite green removal from natural waters and industrial effluents was investigated in this work. For the optimization of experimental variables, a central composite design was used, in which the effect of pH and biosorbent dose was evaluated on biosorption capacity and removal percentage. Optimal parameters of pH 5 and biosorbent dose of 0.80 g L-1 allowed a malachite green removal percentage of 87.7%. Data obtained from kinetic studies were fitted with the pseudo-second-order model. The maximum biosorption capacity was determined using the Langmuir equilibrium model, reaching a value of 214.2 mg g-1. The biosorption process was thermodynamically favorable and spontaneous at room temperature. The calculated value of biosorption enthalpy change indicated that the nature of the process was exothermic and physical. The biosorption process was applied in natural waters and industrial effluent samples, obtaining removal percentages up to 84.3%, which demonstrates the efficiency of grape stalks for the treatment of complex matrices.